Rainforests - Riggs, Kate. (Mankato, Minn. : Creative Education, 2010)
"A fundamental look at a common food chain in the rainforest, starting with the cacao tree, ending with the powerful jaguar, and introducing various animals in between"--Provided by publisher.
"A green book."
Includes bibliographical references (p. 24) and index.
Keywords: Rain forest ecology -- Juvenile literature; Food chains (Ecology) -- Juvenile literature